2010
DOI: 10.4161/oxim.3.3.12070
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Fetal Distress: Potential Prospects for Diagnosis

Abstract: Our aim was to investigate the relation between fetal distress and oxidative stress. Fetal distress was associated with increased concentration of superoxide in the fetal blood and with significant increase of the level of H2O2 in both maternal and fetal blood. The activity of superoxide dismutase was increased roughly sixfold (p < 0.01) in the maternal [7330 ± 2240 U/g of hemoglobin in controls (C) and 36811 ± 16862 U/g in fetal distress (FD)] and fetal blood (C: 5930 ± 2641 U/g; FD: 41912 ± 17133 U/g). In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 46 publications
1
10
0
1
Order By: Relevance
“…This hypothesis is further supported by our findings that gene expression of SLC9B1 is associated with high maternal systolic and diastolic blood pressure, and with a report from the literature that showed preeclampsia, which is characterized by high blood pressure, is associated with abnormal fetal heart rate [30]. Previous studies have also shown increased ROS production in both the mother and fetus is associated with fetal intolerance of labor [31]. Future studies should further examine the role of SLC9B1 in human fertility and pregnancy outcomes, especially in the context of cardiovascular dysfunction.…”
Section: Discussionsupporting
confidence: 90%
“…This hypothesis is further supported by our findings that gene expression of SLC9B1 is associated with high maternal systolic and diastolic blood pressure, and with a report from the literature that showed preeclampsia, which is characterized by high blood pressure, is associated with abnormal fetal heart rate [30]. Previous studies have also shown increased ROS production in both the mother and fetus is associated with fetal intolerance of labor [31]. Future studies should further examine the role of SLC9B1 in human fertility and pregnancy outcomes, especially in the context of cardiovascular dysfunction.…”
Section: Discussionsupporting
confidence: 90%
“…It confirms importance of working on this subject. [23,24] The role of ROS on embryo development is relatively recent field but there are studies confirmed that overproduction of ROS causes altered placental remodeling and abnormal fetal development and growth [25] Other authors demonstrated that maternal and fetal bloods are exposed to oxidative stress in fetal distress [26]. Our analysis of total protein level demonstrated its significantly higher concentrations in patients with high (>1:50) risk of chromosomal aberrations as compared to controls.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, neonates born via Caesarean delivery are predisposed to pathological conditions related to changes in antioxidant levels (Nejad et al, 2016), while increased oxidative stress in neonates contributes to chronic lung disease and neonatal respiratory distress syndrome (Tsukahara et al, 2004). Future research should examine the relationship between increased protein oxidation at the end of term and fetal distress syndrome, characterized by increased reactive oxygen species and lower catalase activity as a consequence of fetal hypoxia (Raicević et al, 2010). Indeed the latter is an indication to Caesarean section.…”
Section: Dependent Variablesmentioning
confidence: 99%